Efficacy, technical parameters and costs of applying insecticide using boom sprayers vs spray lances for controlling melon thrips in orchid nurseries in Thailand - Sampaothong, S.; Punyawattoe, P. (International Journal of Agricultural Technology, 2020)
The application of a vertical boom sprayer and a self-propelled vertical boom sprayer gave similarly effective control melon thrips when compared with a spray lance technique as a conventional sprayer in both field trials. In addition, the technical parameters (spray volume, spraying time spent, amount of insecticide and surfactant) and cost analysis for applying insecticide showed that the boom sprayers was reduced spray volume by 22.2±1.9% to 25.5±3.7%, spraying time spent by 40.2±1.5% to 63.9±1.8%, amount of insecticide and surfactant by 21.7±3.7% to 25.4±3.7%, and operational costs by 27.0±1.7% to 52.9±5.5% when compared with the spray lance. It revealed that the appropriate technique could increase spray application efficiency and achieve the real cost savings for orchid growers.